Freedom and equality in John Rawls’ theory of justice - Bagetti Zeifert, Anna Paula; Rubens Cenci, Daniel; Tonel, Rodrigo (Revista da Faculdade de Direito do Sul de Minas, 2019)
This article analyzes the rawlsian proposal of society as an equitable system of cooperation and the relevance of the notions of freedom and equality as guiding elements of the principles of justice. In this sense, securing stability and the formation of a public reason so that societies might develop in a more just way by reconciling the most varied conceptions of good present within a society is a challenge for the project of social justice in Rawls. Some possibilities for conciliation among these different conceptions of good emerge in this context, demonstrating that it is necessary to strengthen the sense of justice in each subject so that, in the conflict between a conception of unreasonable good, the principles of justice prevail and begin to serve as guide for the establishment of social justice. Thus, based on the hypothetical-deductive approach, using a theoretical basis present in the contemporary political philosophy, the article invites us to reflect on the supposed theorists who structure the rawlsian conception for a just political society. It remains evident that the basic structure, one of the foundations of Rawls’s ideal of social justice, is responsible for confronting injustices, challenging societies to review their actions. As complex as it may be the complete elimination of the contingencies that manifest within social life, it is the responsibility of the institutions to contribute to mitigating such intercurrences and promoting cooperation.